Why Are Some Subsidiaries of Multinationals the Source of Novel Practices while Others Are Not? National, Corporate and Functional Influences. (21st January 2015) - Edwards, Tony; Sanchez‐Mangas, Rocio; Bélanger, Jacques; McDonnell, Anthony
<x xml:space="preserve">Abstract</x> It has frequently been argued that multinational companies are moving towards network forms whereby subsidiaries share different practices with the rest of the company. This paper presents large‐scale empirical evidence concerning the extent to which subsidiaries input novel practices into the rest of the multinational. We investigate this in the field of human resources through analysis of a unique international data set in four host countries – Canada, Ireland, Spain and the UK – and address the question of how we can explain variation between subsidiaries in terms of whether they initiate the diffusion of practices to other subsidiaries. The data support the argument that multiple, rather than single, factor explanations are required to more effectively understand the factors promoting or retarding the diffusion of human resource practices within multinational companies. It emerges that national, corporate and functional contexts all matter. More specifically, actors at subsidiary level who seek to initiate diffusion appear to be differentially placed according to their national context, their place within corporate structures and the extent to which the human resource function is internationally networked.